1996
DOI: 10.1016/0736-5748(96)00001-9
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral neurochemical alterations and immune effects of prenatal ethanol exposure in rats

Abstract: In contrast to the well known effects of prenatal ethanol exposure on the central nervous system, data about its peripheral effects are scarce. Here, Sprague Dawley rats were fed a liquid diet (gestational days 0-20) containing 36% ethanol-derived calories (EDCs, group H) or were pair-fed with 18% EDCs (group L) or 0% EDCs (group C). On postnatal day 20, one male and one female from each of 10 litters per group were killed. Norepinephrine (NE) was analyzed in the frontal cortex, spleen and thymus, and dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Zafar et al (2000) found that 21-day-old E females had a transient decrease in 5-HT transporter binding sites in the hypothalamus compared to control females, although 21-day-old male offspring were not affected. Clausing et al (1996) found a decrease in striatal 5-HT and 5-HIAA in 20-day-old E females, but not in E males. A third study found that females exposed to ethanol in the early postnatal period (third trimester equivalent) showed increased basal levels of septal 5-HT and 5-HIAA in adulthood (Kelly 1996).…”
Section: Discussionmentioning
confidence: 82%
“…Zafar et al (2000) found that 21-day-old E females had a transient decrease in 5-HT transporter binding sites in the hypothalamus compared to control females, although 21-day-old male offspring were not affected. Clausing et al (1996) found a decrease in striatal 5-HT and 5-HIAA in 20-day-old E females, but not in E males. A third study found that females exposed to ethanol in the early postnatal period (third trimester equivalent) showed increased basal levels of septal 5-HT and 5-HIAA in adulthood (Kelly 1996).…”
Section: Discussionmentioning
confidence: 82%
“…The fact that no significant differences were observed in cytokine response to various immune challenges in C and E animals has important implications. It suggests that changes in the release of these cytokines probably does not underlie the altered immune function that has been observed in animals that have been exposed to alcohol prenatally (Gottesfeld et al, 1990;Gottesfeld and Ullrich, 1995;Chiappelli and Taylor, 1995;Giberson and Weinberg, 1995;Clausing et al, 1996;Jerrells and Weinberg, 1998).…”
Section: Discussionmentioning
confidence: 94%
“…Data primarily from these animal models have shown that perinatal ETOH exposure can affect virtually every neurotransmitter and neuromodulator that has been studied including the monoamines dopamine, norepinephrine, and serotonin (e.g. Boggan et al, 1996;Clausing et al, 1996;Maier et al, 1996;Shen et al, 1999;Sobrian et al, 2005;Tran and Kelly, 1999;), adenosine (Othman et al, 2002), the neurosteroids, opioids (Angelogianni and Gianoulakis, 1989) and the amino acid transmitters GABA and glutamate (GLU) (e.g. Diaz-Granados et al, 1997;Hsiao et al, 1998;Spuhler-Phillips et al, 1997).…”
mentioning
confidence: 99%